OPTIMALISASI PENEGAKAN HUKUM TERHADAP KEJAHATAN PERBANKAN DENGAN MENERAPKAN UNDANG-UNDANG TINDAK PIDANA PENCUCIAN UANG DI KEPOLISIAN DAERAH RIAU - Triya Yunita Permata Sari; Mukhlis R; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The results of an interview with the investigators at Sub-Directorate II of the Riau Regional Police's Special Criminal Investigation Directorate, Mr. IPDA Dedi Suharyoso, the was a criminal act that occurred at BRI bank unit Seikijang, during the course of the case investigator found money laundering from banking crime, but when the file arrived at the public prosecutor the case turnet into a corruption case. And other cases that were also handled case of the BJB bank where one of its employees succeeded in breaking into money to choose a customer. up to billions of rupiah. So there needs to be an effort to optimize law enforcement against banking crimes with a money laundering approach in order to trace the flow of funds and arrest parties who participate or enjoy the proceeds of crime.This type of research is classified as sociological legal research. While the population and sample were parties related to the problem being studied such as Heads of Offices, Panits and Investigators in Subdit II of the Riau Regional Police Special Criminal Research Directorate, the data source used is primary data, while the data collection techniques in this study were carried out by interviews and literature study.The results of the research show that law enforcement against banking crimes using the money laundering approach is still not optimal. Becauce there are several factors that influence, namely the weak role of the banking sector, investigation doubts about whether or not there is money laundering from predominantly banking crimes, lack of coordination between the police and various related agencies, differentces of opinion between law enforcers in determining banking crimes related to money laundering.Keywords: Law Enforcement, Banking Crime, Money Laundering